Advanced materials : proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2018 /: proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2018. (2019) - Unknown
No abstract available